Native language interference in learning english as foreign language: an analysis of written material produced by spanish speaking students in senior high school classes. - Manuel, Garcia (2010)
The present research work aims to help the audience understand why this interference occurs and how frequently it does. A deep study on language acquisition and an error analysis will be carried out in order to conduct a field research through questionnaires and stories creation, be able to identify why these mistakes occur and find a way to overcome them; giving, in this way, a better insight to the understanding of these errors origins and help teachers with tools and techniques to help reduce the amount of interference errors in class and in learners of english as a foreign language.